Implementation of Vector Space Model in Online Jobs Vacancy Aggregator - Awaliyah Zuraiyah, Tjut; elli Wihartiko, Fajar D; Effendi, Edwin (International Journal of Engineering and Technology, 2018)
Job vacancy aggregator is a system that facilitates users in finding the desired job vacancy, especially in the field of information technology.Â Job vacancy data collected from various job sites such as http://id.jobsdb.com, http://www.jobs.id, http://www.monster.co.id and http://www.jobstreet.co.id using web scraping techniques to extract job vacancy data that is stored in the HTML structure.Â The collected data is then processed to facilitate the retrieval concept by vector space model method, by using vector space model data which is found to be sorted based on the similarity level between the query which is typed by the user with the job vacancy data is stored in the database.Â In addition system can also perform email jobs sent via email to registered users.Â With the development of an online job vacancy aggregator, it can be used as a media job vacancy information, especially in the field of information technology (IT). Â Â